The carboniferous geology of the Dublin area - Nolan, S. C. (Trinity College (Dublin, Ireland). Department of Geology, 1987)
The Carboniferous (Courceyan to Arnsbergian) sedimentary rocks of the Dublin area, between the Balbriggan and Leinster Massifs, are described and discussed. The region north of Swords was re-mapped at a scale of 1:10,560 while the region to the south was studied at a reconnaissance level. Outcrop and borehole material was utilised across the whole area. A revised lithostratigraphy is presented. The geographical extent of the revised formations is shown in detail on two 1:25,0OO solid geological maps and one 1:126,720 geological sketch map. The disposition of Carboniferous strata on the coastal section north of Rush is shown in detail on maps and cross-sections at a scale of 1:2,500. Sedimentological and petrographical studies were undertaken to investigate the geological development of the Dublin Basin. A wide range of basinal facies, ranging from coarse debris flow fans to non-point sourced turbidity current and storm underflow deposits, are recognised. The sedimentology of fluviatile and shallow marine carbonate shelf facies present are also briefly described. Analysis of the data indicates that the Dublin Basin developed in an extensional regime and that overall it gradually expanded in extent from the late Courceyan to early Namurian. Structural work was undertaken at a preliminary level. Analysis of the area indicates deformation by Hercynian transpression and indicates that part of the area has undergone significant clockwise rotation. Foraminiferal biostratigraphy was employed as a control: A number of genera and species are recorded from Ireland for the first time. The thesis comprises two volumes of text, figures and plates, and a box containing seventeen enclosures which include measured lithological sections and solid geological maps. The second volume is an appendix devoted mostly to systematic description and discussion of microscopic foraminiferal and algal fossils.
Access restricted on volume 3 due to image copyright concerns. Please consult print copy in the Library.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin